2018
DOI: 10.1186/s13661-018-1008-9
|View full text |Cite
|
Sign up to set email alerts
|

On high order fractional integro-differential equations including the Caputo–Fabrizio derivative

Abstract: By using the fractional Caputo-Fabrizio derivative, we introduce two types new high order derivations called CFD and DCF. Also, we study the existence of solutions for two such type high order fractional integro-differential equations. We illustrate our results by providing two examples.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
104
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 160 publications
(104 citation statements)
references
References 12 publications
0
104
0
Order By: Relevance
“…x(t) as = A cos(Ωt + φ). (27) From the system transfer function H 10 , the expressions of the steady-state response amplitude and phase shift of the system can be obtained:…”
Section: Steady-state Response Of the First Moment And Output Amplitudementioning
confidence: 99%
See 1 more Smart Citation
“…x(t) as = A cos(Ωt + φ). (27) From the system transfer function H 10 , the expressions of the steady-state response amplitude and phase shift of the system can be obtained:…”
Section: Steady-state Response Of the First Moment And Output Amplitudementioning
confidence: 99%
“…For most of the real systems, such as viscoelastic processes, however, the damping term no longer depends only on the current speed but also the historical speed, i.e., one has to take into account the memory effects. Meanwhile, the fractional derivative, naturally has a good ability to describe such memory property [20][21][22][23][24][25][26][27]. Therefore, we proposed a power-law kernel function to model such processes which are associated with the Caputo fractional derivative.…”
Section: Introductionmentioning
confidence: 99%
“…Quadratic perturbation in fractional differential equations (FDEs) has become a significant tool to model many physical phenomena in physics, biology, engineering, and control theory. Some recent developments can be found in a series of papers . It is observed that a class of DEs representing certain physical phenomenon may not be easily solvable or analyzed.…”
Section: Introductionmentioning
confidence: 99%
“…Some recent developments can be found in a series of papers. [1][2][3][4][5][6][7][8][9][10] It is observed that a class of DEs representing certain physical phenomenon may not be easily solvable or analyzed. However, employing perturbations in such problems makes it possible to study with available methods.…”
Section: Introductionmentioning
confidence: 99%
“…In the last two years, many authors used Caputo-Fabrizio fractional derivative operator in many interesting models and with many known methods, see [11][12][13][14][15][16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%